Intravenous Drug Abuse by Patients Inside the Hospital: A Cause for Sustained Bacteremia - Noopur Goel; Lubna Bashir Munshi; Braghadheeswar Thyagarajan (Case Reports in Infectious Diseases)
Patients with history of intravenous drug abuse are noted to be at risk of several infections including HIV, endocarditis, and other opportunistic infections. We report the case of a patient with sustained Bacillus cereus bacteremia despite use of multiple antibiotic regimens during his inpatient stay. Our case highlights the importance of high suspicion for active drug use inside the hospital in such patients. This is important in order to minimize unnecessary diagnostic workup and provide adequate treatment and safe hospital stay for these patients.